2021
DOI: 10.1021/acsomega.1c04909
|View full text |Cite
|
Sign up to set email alerts
|

ICG-Loaded PEG-Modified Black Phosphorus Nanosheets for Fluorescence Imaging-Guided Breast Cancer Therapy

Abstract: Indocyanine green (ICG) has been used in various surgical navigation systems and plays an important role in intraoperative imaging diagnosis. However, the poor photostability and unsatisfactory tumor-targeting ability have limited its broad application prospects. In the decades, the construction of a nanodrug delivery system for tumor-targeting diagnosis and therapy has become a research hotspot. Black phosphorus nanosheets (BPNS), as a new kind of biodegradable nanomaterials, have the advantages of high loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The characteristic peaks were observed at 3415 and 3284 cm –1 for N–H stretching bonds and at 1620 cm –1 for the CC stretching bond for the PDA polymer modified on PLNP–OH . The characteristic peak at 1415 cm –1 was related to the N–H vibration bond and that at 1103 cm –1 for the C–O stretching bond, illustrating that ICG was loaded as PLNP–PDA–ICG …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The characteristic peaks were observed at 3415 and 3284 cm –1 for N–H stretching bonds and at 1620 cm –1 for the CC stretching bond for the PDA polymer modified on PLNP–OH . The characteristic peak at 1415 cm –1 was related to the N–H vibration bond and that at 1103 cm –1 for the C–O stretching bond, illustrating that ICG was loaded as PLNP–PDA–ICG …”
Section: Resultsmentioning
confidence: 94%
“…39 The characteristic peak at 1415 cm −1 was related to the N−H vibration bond and that at 1103 cm −1 for the C−O stretching bond, illustrating that ICG was loaded as PLNP− PDA−ICG. 40 The hydrodynamic size and zeta potential were also recorded. The average size of PLNP−OH was 91.3 nm and increased to 106 nm for PLNP−PDA.…”
Section: Characterization Of Plnp−pda−icgmentioning
confidence: 99%
“…Ma. et al combined ICG with black phosphorus nanosheets, enabling the nanodrug delivery system to have fluorescence imaging capability and almost no change in the optical stability of ICG (Pan et al, 2021). To compensate for the deficiency of ACQ effect of heptamethine cyanine dyes, Meng et al introduced an aggregation‐induced emission unit into the IR‐780 structure to synthesize IR‐780 derivatives with enhanced aggregated‐induced emission (AIE) properties (Zhao et al, 2020).…”
Section: Heptamethine Cyanine Dye‐based Tumor Imagingmentioning
confidence: 99%
“…For example, ICG-loaded PEGylated liposome (PEG-Lip-ICG) was developed to localize rectal tumors . Some inorganic nanocomposites such as ICG-loaded PEGylated black phosphorus nanosheets (BPNS-PEG) were also prepared for tumor targeting and photothermal therapy . Although ICG and its derivatives have been applied to image the tumor tissue, it has been observed that ICG mainly accumulates in the liver and partly in the gastrointestinal tract, lymph nodes, spleen, or kidney .…”
Section: Introductionmentioning
confidence: 99%